Association of Age at Onset and First Symptoms With Disease Progression in Patients With Metachromatic Leukodystrophy. (12th January 2021) - Kehrer, Christiane; Elgün, Saskia; Raabe, Christa; Böhringer, Judith; Beck-Wödl, Stefanie; Bevot, Andrea; Kaiser, Nadja; Schöls, Ludger; Krägeloh-Mann, Ingeborg; Groeschel, Samuel
Abstract : Objective: To compare disease progression between different onset forms of metachromatic leukodystrophy (MLD) and to investigate the influence of the type of first symptoms on the natural course and dynamic of disease progression. Methods: Clinical, genetic, and biochemical parameters were analyzed within a nationwide study of patients with late-infantile (LI; onset age ⩽2.5 years), early-juvenile (EJ; onset age 2.6 to <6 years), late-juvenile (LJ; onset age 6 to <16 years), and adult (onset age ≥16 years) forms of MLD. First symptoms were categorized as motor symptoms only, cognitive symptoms only, or both. Standardized clinical endpoints included loss of motor and language functions, as well as dysphagia/tube feeding. Results: Ninety-seven patients with MLD were enrolled. Patients with LI (n = 35) and EJ (n = 18) MLD exhibited similarly rapid disease progression, all starting with motor symptoms (with or without additional cognitive symptoms). In LJ (n = 38) and adult-onset (n = 6) patients, the course of the disease was as rapid as in the early-onset forms, when motor symptoms were present at disease onset, while patients with only cognitive symptoms at disease onset exhibited significantly milder disease progression, independently of their age at onset. A certain genotype-phenotype correlation was observed. Conclusions: In addition to age at onset, the type of first symptoms predicts the rate of disease progression in MLD. These findings are important for counseling and therapy. Classification of Evidence: This study provides Class II evidence that in patients with MLD, age at onset and the type of first symptoms predict the rate of disease progression.